Basic Concept of Ophthalmology and Visual Disorder - Liliyanti Fauzi; Tiara Bunga (Sriwijaya Journal of Ophthalmology, 2022)
The eye is a complex sensory organ that is responsible for vision. Within the protective sheath, each eye has receptors, a lens system for focusing light on receptors, and a nervous system for transmitting impulses from the receptors to the brain. Visual dysfunction can be caused by abnormal eye movements or changes in visual acuity, refraction, color vision, or accommodation. Visual dysfunction may also be a secondary effect of other neurological disorders. This narrative review aims to describe the structure of the eye in general and visual disturbances caused by the aging process and disorders of the protective structure of the eye.